(untitled) (Journal of Artificial Intelligence & Research, 2023)
Evolutionary optimization techniques play a vital role in solving complex optimization problems in artificial intelligence (AI). These techniques, inspired by natural evolution, have been successfully applied to various domains, including machine learning, robotics, and data mining. This paper provides an overview of evolutionary optimization techniques, including genetic algorithms, genetic programming, evolutionary strategies, and differential evolution. It explores their principles, advantages, and limitations, as well as their application in solving optimization problems in AI. The paper also discusses recent advancements and future directions in evolutionary optimization research, highlighting the potential of these techniques to further enhance the capabilities of AI systems.